- 1-214-256-5804
- info@tutorpace.com

Given points: A (2, 3) and B (4, 5)

Midpoint of a line, (x, y) = [(x

Here given point A= (x

This gives: midpoint of the line AB = (x, y) = [(2+ 4)/2, (3+ 5)/2] = (6/2, 8/2) = (3, 4)

Hence the midpoint of the given line AB is (3, 4).

Given points: X (-1, 4) and Y (3, -6)

Midpoint of a line, (x, y) = [(x

Here given point X= (x

This gives: midpoint of the line XY = (x, y) = [(-1 + 3)/2, (4+ (- 6))/2] = (2/2, -2/2) = (1, -1)

Hence the midpoint of the given line XY is (1, -1).